PEMANFAATAN INTERNET SEBAGAI MEDIA BELAJAR KEPADA GURU TAMAN KANAK KANAK DI TANJUNG PIAYU KOTA BATAM: Utilization of the Internet as a Learning Medium for Kindergarten Teachers in Tanjung Piayu Batam - Rika Harman; Amrizal Amrizal; Nopriadi Nopriadi; Sasa Ani Arnomo (ASOSIASI IDEBAHASA KEPRI, 2023)
Information and communication technology is growing rapidly. Information technology enters various fields ranging from the world of offices to medicine, business, the arts, culture, and many other fields, including education. In the world of education, there are many ways to take advantage of information technology, from making learning media to the learning process to presenting the material in the learning itself. All can rely on information technology; all that remains is to choose which technology is suitable to use. New problems arise when teachers cannot utilize the media. They continue to rely on traditional and outdated learning media. So it is certain that the material produced is less interesting and seems boring. In addition, today's students focus more on what they see. If you provide a special attraction, it will automatically impress them. In this training, the target is PAUD teachers. They will be given training on how to use the internet as a learning resource for their students. Many internet sites can be used as learning media. The material that will be delivered can be in the form of getting to know letters, knowing numbers, getting to know animals, getting to know plants, and much more. If you have to present material on the internet, of course you can't display it right away because it will take time. This is due to the advertisements that appear and other disturbances that must be transferred to the display media, such as Microsoft PowerPoint. Methods like these must be mastered by a teacher. The target of this training itself is to be able to use the internet as a learning medium and also use it for various other needs. This service activity was successfully carried out, and the results can be seen in the increased skills of the trainees in utilizing the internet as a learning medium. With this skill, it will certainly have an impact on the quality of learning and the material provided. The material provided becomes more varied and not boring.